SOCIAL MEDIA MARKETING STRATEGY IN BUILDING BRAND ENGAGEMENT - Malida Zulfaniazahra Riski; Muhammad Edy Susilo; Kartika Ayu Ardhanariswari (The Indonesian Journal of Communication Studies, 2021)
The rapid development of social media as part of people’s lifestyle nowadays, is currently being used by companies to strengthen emotional bonds between consumer and brand. Through social media marketing activities in #AlamiLawanJerawat campaign, &friends as a creative agency carried out three objective phases, one of them is brand engagement, which is an important element in getting consumer participation. This study aims to find out the social media marketing strategy and explore the factors which oppose the social media marketing strategy of &friends in building Himalaya’s brand engagement through #AlamiLawanJerawat campaign on Instagram. This study used Breakenridge's The Social Media Strategy Wheel theory with the concept of brand engagement. This research method used descriptive qualitative case study. The data collection process was carried out by observation and in-depth interview. From the research results, it was found that the strategy taken by &friends for Himalaya was to create insights for content creation related to target audiences, utilize influencer channels, and engagement contents such as giveaway and honest reviews which ultimately succeeded in increasing brand engagement at the loyalty audiences stage, with 217% increase in sales in four months, and a growth of  followers from 15,000 to 27,000 after the #AlamiLawanJerawat campaign on Instagram. In implementing the strategy, internal obstacles were found, namely inconsistencies in the implementation of the content schedule and external obstacles on the timeline production.